2022
DOI: 10.3390/w14040559
|View full text |Cite
|
Sign up to set email alerts
|

Alum and Gypsum Amendments Decrease Phosphorus Losses from Soil Monoliths to Overlying Floodwater under Simulated Snowmelt Flooding

Abstract: Phosphorus (P) loss from soils poses a threat of eutrophication to downstream waterbodies. Alum (Al2(SO4)3·18H2O) and gypsum (CaSO4·2H2O) are effective in reducing P loss from soils; however, knowledge on their effectiveness under cold temperatures is limited. This study examined the reduction of P loss from soils with alum and gypsum amendment under simulated snowmelt flooding. Intact soil monoliths (15 cm depth) collected from eight agricultural fields in flood-prone areas of Manitoba, Canada, were surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 66 publications
4
16
4
Order By: Relevance
“…By the end of the sampling campaign (42 DAF), Eh of the soils had declined by 176-460 mV resulting in Eh ranging from 59 to 329 mV for all soils, regardless of alum amendment. The Eh decrease was lower in the current study with widely fluctuating air temperatures, than was observed by Kumaragamage et al (2022) that used a single, controlled, air temperature. The rate at which saturated soils become reduced is greater at higher temperature (Vaughan et al, 2009).…”
Section: Changes In Redox Potentialcontrasting
confidence: 90%
See 4 more Smart Citations
“…By the end of the sampling campaign (42 DAF), Eh of the soils had declined by 176-460 mV resulting in Eh ranging from 59 to 329 mV for all soils, regardless of alum amendment. The Eh decrease was lower in the current study with widely fluctuating air temperatures, than was observed by Kumaragamage et al (2022) that used a single, controlled, air temperature. The rate at which saturated soils become reduced is greater at higher temperature (Vaughan et al, 2009).…”
Section: Changes In Redox Potentialcontrasting
confidence: 90%
“…Overall, the floodwater DRP concentrations in this study (averaged across soils for each sampling time) were 1.8-7.3-fold of the floodwater DRP concentrations measured in our previous study (Kumaragamage et al, 2022) conducted with flooded, intact monoliths from the same locations and time but incubated at a constant temperature of 4˚C. The higher DRP concentrations in this current study than Kumaragamage et al (2022) may be due to the multiple soil freeze-thaw events between day and night. Our results imply that there is a high risk of losing P to overlying floodwater during spring snowmelt in cold regions irrespective of the air temperature during the flooding event.…”
Section: Changes In Concentrations Of Porewater and Floodwater Dissol...supporting
confidence: 40%
See 3 more Smart Citations